Carbon’s social cost can’t be retrofitted to water - Wheeler, Sarah; Ringler, Claudia; Garrick, Dustin (Springer, 2023)
This Nature comment focuses on the concept of the social cost of water that was suggested during the 2023 UN Water Conference. It notes that the concept has significant challenges. Emphasis should instead be focused on local management and institutions.